THE CORRELATION BETWEEN ENGLISH SPEAKING ANXIETY AND STUDENTS’ SPEAKING PERFORMANCE AT MA NURUL FALAH AIR MOLEK - M Jihad Arrasyid; Destri Wahyuningsih; Silviana Masran; Riza Astriani (Ensiklopedia Research and Community Service Review, 2026)
This study investigated the correlation between English speaking anxiety and students’ speaking performance among tenth-grade students at MA Nurul Falah Air Molek. The research aimed to determine the level of students’ English speaking anxiety, describe their speaking performance, and examine the significance, strength, and direction of the relationship between the two variables. A quantitative approach with a correlational research design was employed. The participants consisted of 60 tenth-grade students. Data on English speaking anxiety were collected through a questionnaire adapted from the Foreign Language Classroom Anxiety Scale, while speaking performance scores were obtained from the English teacher’s assessment records. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, a linearity test, and Pearson Product-Moment correlation with SPSS. The results showed that students’ English speaking anxiety was in the moderate category, with a mean score of 89.07 and a standard deviation of 9.690. A total of 63.33% of the students experienced moderate anxiety. Students’ speaking performance was also predominantly moderate, with a mean score of 75.35 and a standard deviation of 10.338; 65.00% of the students were classified in this category. The correlation analysis produced a coefficient of 0.614 with a significance value of p 0.001, indicating a strong, positive, and statistically significant correlation between English speaking anxiety and speaking performance. The coefficient of determination showed that the variables shared 37.70% of their variance. It was concluded that English speaking anxiety was significantly associated with students’ speaking performance, although the correlational design did not establish a causal relationship.Keywords: anxiety, speaking, performance